Effects of putrescine, spermidine and spermine on growth and serum lipid levels in sprague-dawley rat offspring - Mert Biberoğlu, Fatma; Büyükuslu, Nihal (Istanbul Medipol University, 2022)
Polyamines are short-chain, basic biogenic amines that are essential for cell growth and reproduction. This study was conducted to examine the effects of maternal polyamine intake on growth and serum lipid levels in first generation rat offspring. Female Sprague-Dawley rats (n=35) of 8 weeks old were used in the study. Rats were divided into five groups according to the polyamine they are fed as putrescine, spermidine, spermine, putrescine-spermidine-spermine, and control group. Before pregnancy, during pregnancy and lactation polyamines were administered to rats by oral gavage. After the offsprings were born, weights were measured every two days. Blood samples were taken when they were one month old and serum lipid analyzes were performed. When the groups were compared with the control group, it was shown that spermidine and spermine significantly increased the total cholesterol level, spermidine and putrescine-spermidine-spermine significantly decreased the triglyceride level and significantly increased the HDL level of the spermine. When birth weight averages and final weight averages were compared, it was seen that the group given putrescine-spermidine-spermine had the highest value. In conclusion, this study shows the effects of maternal polyamine intake on growth, total cholesterol, HDL, LDL and triglyceride levels of rat offsprings.
Keywords: Lipid Profile; Polyamine; Putrescine; Spermidine; Spermine